Memory effects in funnel ratchet of self-propelled particles. (12th May 2017) - Hu, Cai-Tian; Wu, Jian-Chun; Ai, Bao-Quan
Abstract: The transport of self-propelled particles with memory effects is investigated in a two-dimensional periodic channel. Funnel-shaped barriers are regularly arrayed in the channel. Due to the asymmetry of the barriers, the self-propelled particles can be rectified. It is found that the memory effects of the rotational diffusion can strongly affect the rectified transport. The memory effects do not always break the rectified transport, and there exists an optimal finite value of correlation time at which the rectified efficiency takes its maximal value. We also find that the optimal values of parameters (the self-propulsion speed, the translocation diffusion coefficient, the rotational noise intensity, and the self-rotational diffusion coefficient) can facilitate the rectified transport. When introducing a finite load, particles with different self-propulsion speeds move to different directions and can be separated.